Initial incorporation of phytoplankton into young ice in Saroma Ko lagoon, Hokkaido, Japan - Niimura,Yoko; Ishimaru, Takashi; Taguchi,Satoru (National Institute of Polar Research, 2000)
P(論文) The initial incorporation of phytoplankton into young ice was examined on February 25-28,1998 in Saroma Ko lagoon, Hokkaido, Japan to test our hypothesis that some physical selection would occur to establish the ice algal assemblages during the formation of young sea ice and the development of fast sea ice. An open pool (2×2m) was employed for the experiment. Young sea ice was collected for a 24hr experiment. Relative brine volume in the young sea ice might be related to air temperature. Incorporated contents of chlorophyll α, biogenic silica, particulate organic carbon and nitrogen were directly related to the relative brine volume. The larger than 2μm fractions of chlorophyll α and biogenic silica were 95% and 78%, respectively. The most abundant species incorporated into the young sea ice were Navicula transitans (33%) and Achnanthes taeniata (12%). Those species were originated from a water column where they were released from the bottom surface of seasonal sea ice in the vicinity of the experimental pool. Cell density of the incorporated phytoplankton ranged from 46 to 154 cells ml^<-1> into the young sea ice and 17±5 cells ml^<-1> in the sea water under the young sea ice. Those microscopic observations suggested the selective incorporation of phytoplankton into the young sea ice at the beginning of ice formation and it might accelerate selective development of establish the ice algal assemblages with the growth of fast sea ice. departmental bulletin paper